The complex crosstalk between inflammatory cytokines and ventricular arrhythmias. (November 2018) - Kouvas, N.; Kontogiannis, C.; Georgiopoulos, G.; Spartalis, M.; Tsilimigras, D.I.; Spartalis, E.; Kapelouzou, A.; Kosmopoulos, M.; Chatzidou, S.
Highlights: Cytokines present a non-linear relationship with arrhythmogenic potential of myocardium. Cytokines affect the autonomic innervation of the heart. Serum cytokine levels predict the occurrence of arrhythmia after infarction. Serum cytokine levels affect the outcome of Cardiac Resynchronization Therapy. Abstract: The network of cytokines consists one of the most extensively studied signaling systems of human body. Cytokines appear to modulate pathogenesis and progress of many different diseases in the human body, particularly in regards to cardiovascular system. However, their effects on the electrical system of the heart has been neglected. Over the past decade, attemps to understand this relationship led to the uncovering of the direct and indirect effects of cytokines on action potential propagation and cell depolarization. This relationship has been depicted in clinical practice as serum levels of cytokines are increasingly associated with prevalence of ventricular arrhythmias either isolated or secondary to either a heart condition or a systemic auto-immune disease. Thus, they present an appealing potential as a biomarker for prediction of arrhythmia generation, as well as the ourtcome of electrophysiological interventions.